Analisis Makna Semantik dalam Syi’ir Tanpo Waton Karya KH. Muhammad Nizam As-Shofa - Nuriel Shiami Indiraphasa; Ni Gusti Ayu Roselani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze seven semantic meanings in Syi'ir Tanpo Waton by KH Muhammad Nizam As-Shofa using Leech's theory of meaning. The method used is descriptive qualitative, with data in the form of words, phrases, and sentences in the text of the poem accessed through the NU Online page. The results of the study indicate that Syi'ir Tanpo Waton contains various types of semantic meanings, namely conceptual, connotative, social, affective, reflective, collocative, and thematic meanings. The most dominant conceptual and connotative meanings describe the vertical relationship between humans and God, as well as deep spiritual values. The social meaning emphasizes inclusiveness and Javanese culture, while the affective meaning reflects religious emotions in the form of praise, prayer, and hope. The reflective meaning shows layers of multiple meanings, while the collocative meaning builds associations of related words. Thematic meaning emphasizes the urgency of worship, knowledge, and praise to God as the main themes.